1996
DOI: 10.1051/apido:19960101
|View full text |Cite
|
Sign up to set email alerts
|

Grooming behavior and damaged mites (Varroa jacobsoni) in Apis cerana cerana and Apis mellifera ligustica

Abstract: Summary — Varroa mite mortality and mite damage in colonies of Apis cerana cerana Fabr and Apis mellifera ligustica Spin, where mites were added to observation hive bees and to full-sized colonies of both bee species, were studied. The results show grooming behavior in A cerana but the results also indicate that this behavior may be less effective than previously recorded. In A mellifera colonies, phoretic mites were also removed by the bees but less effectively than in A cerana colonies. The proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 6 publications
3
71
1
2
Order By: Relevance
“…The ability of A. cerana to maintain Varroa mite infestations at low levels is supposedly due to Varroa mite reproduction being limited to drone brood as well as the grooming and hygienic behaviour exhibited by their workers (Koeniger et al 1983;Peng et al 1987;De Jong 1988;Büchler et al 1992;Rath 1999). Adult honeybees are able to sense mite parasitised brood and they are very efficient at killing mites and eliminating them from colonies (Peng et al 1987; but see Fries et al 1996). The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of A. cerana to maintain Varroa mite infestations at low levels is supposedly due to Varroa mite reproduction being limited to drone brood as well as the grooming and hygienic behaviour exhibited by their workers (Koeniger et al 1983;Peng et al 1987;De Jong 1988;Büchler et al 1992;Rath 1999). Adult honeybees are able to sense mite parasitised brood and they are very efficient at killing mites and eliminating them from colonies (Peng et al 1987; but see Fries et al 1996). The European honeybee does not express these traits at a level at which they confer tolerance to the parasite ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that honey bees are able to kill and injure Varroa females (Ruttner and Hänel, 1992) (Moosbeckhofer, 1992;Büchler, 1993;Wallner, 1994). However, it is still unknown to what degree an enhanced grooming behaviour contributes to a balanced host-parasite relationship (Fries et al, 1996) ('control') In this group the queens were not caged. Otherwise the colonies were treated as described for group 2 (treated brood).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for this has been shown both at the colony level (Arechavaleta-Velasco & Guzmán-Novoa, 2001;Guzmán-Novoa, Emsen, Unger, Espinosa-Montaño, & Petukhova, 2012;Mondragó n, Spivak, & Vandame, 2005;Rinderer et al, 2001) and through assays inoculating individual bees with mites (Aumeier, 2001;Büchler, Drescher, & Tornier, 1992;Fries, Huazhen, Wei, & Jin, 1996;Guzmán-Novoa et al, 2012;Peng, Fang, Xu, & Ge, 1987). These are reviewed in detail by Rinderer et al (2013), and also see Pritchard (2016).…”
Section: Original Research Articlementioning
confidence: 98%
“…In A. mellifera, auto-grooming seems to be the most frequently observed behavior in response to mites (Aumeier, 2001;Fries et al, 1996). This typically involves bees wiping their body with their legs, but can include the bees grasping mites with their mandibles (Boecking & Spivak, 1999;Guzmán-Novoa et al, 2012).…”
Section: Original Research Articlementioning
confidence: 99%